Aquatic environment / (Acc. 4089) - Gautam, Ashutosh, 1965- (New Delhi : Ashish Pub. House, 1992)
Contributed articles covering various aspects of ecology, pollution, and conservation of aquatic environment and resources in India.
Keywords: Aquatic ecology; Water; Aquatic resources conservation; Water conservation; Stream conservation